THE EFFECT OF SHIFT WORK AND WORK STRESS ON EMPLOYEE PERFORMANCE OF SALES ASSOCIATES AT NEW BALANCE MALL THE PARK SEMARANG - Tafan Yunior Satatoe; Syamsul Hadi (Journal of Management Small and Medium Enterprises (SMEs), 2026)
This study analyzes the effect of shift work and work stress on the performance of sales associates at New Balance Mall The Park managed by Mitra Adi Perkasa. The research applies a quantitative approach using questionnaires distributed to employees through a saturated sampling technique. The collected data were analyzed using multiple linear regression. The results show that shift work has a positive influence on employee performance, indicating that an effective shift system can support better work outcomes for employees. In contrast, work stress has a negative influence on employee performance, meaning that higher levels of stress may reduce employees’ ability to perform their tasks effectively. When examined together, shift work and work stress simultaneously influence employee performance. This study provides insights for management in the retail sector to design more effective shift work systems and implement stress management strategies in order to improve employee performance and maintain a productive work environment. Keywords: Shift Work; Work Stress; Employee Performance; Sales Associate; Retail Management